The Relationship Between Social Class and Generalized Trust: The Mediating Role of Sense of Control - Qiang, Ruichao; Li, Xiang; Han, Qin (Frontiers in Psychology, 2021)
The success and well-being theory of trust assumes that social class is associated with individual' s generalized trust. The study extends this assumption to explore the mediating mechanism in the association. We hypothesized that social class will positively predict generalized trust and that the relationships would be mediated by people’s sense of control. Self-report data were collected from a sample of 492 Chinese citizens. The results and mediation analysis support the hypotheses. In sum, this research provides further evidence for success and well-being theory of trust and directs to the key role of sense of control. Limitations and possible future research are discussed.